Double burden of malnutrition and its associated factors in urbanized indigenous peoples (Orang Asli) of Peninsular Malaysia - Mohd Shariff, Zalilah; Ismail, Rozalina; Mohd Shukri, Nurul Husna (Routledge, 2024)
Double burden of malnutrition (DBM) is a global public health concern. This study determined the prevalence of DBM and its associated factors among 451 indigenous households in an urbanized state of Malaysia. Mothers and children were measured for weight and height/length. Mothers were interviewed for socio-demographics and diets of mothers and children. Prevalence of DBM (overweight/obese mother and underweight/stunted child) was 28.8%. Food insecurity, maternal height (<150 cm) and energy intake (>recommendation), child’s age (≥24 months) and energy intake (<recommendation) were significantly associated with DBM. Prevention of DBM in indigenous population should consider strategies that aim to eradicate both poverty and malnutrition.